Waste Management Strategies in the Tofu Industry through Green Accounting Approaches - Dida Farida Latipatul Hamdah; Hanifah Fauziah (UIN Sunan Gunung Djati, 2025)
The tofu industry in Suci Village, Karangpawitan District, Garut Regency, contributes significantly to the local economy, but also causes environmental problems due to suboptimal waste management. This study aims to evaluate the implementation of green accounting and identify the potential for green innovation in tofu industry waste management in Suci Village. The research method used is descriptive qualitative with a case study approach, where data validity is tested using source triangulation techniques to ensure data accuracy and reliability. The results show that most tofu industries have utilized solid waste as animal feed, but liquid waste management is still a major challenge. This study recommends the development of an integrated waste management system, including the construction of a communal Wastewater Treatment Plant (WWTP) and the utilization of liquid waste to produce value-added products such as biogas and organic fertilizer. The implementation of green accounting and green innovation is expected to improve the environmental and economic sustainability of the tofu industry and contribute to the achievement of the Sustainable Development Goals (SDGs) particularly SDG 6 (Clean Water and Sanitation), SDG 9 (Industry, Innovation and Infrastructure), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action).